(untitled) (Journal of Engineering, 2010)
An experimental and theoretical investigation of the effect of flow separation on the performance of a cascade NACA 65_(12)10 axial compressor blade has been carried out. The experimental work includes the fabrication of three blades from wood, each having a chord (100mm) but one of these blades having a span of (90mm) for smoke tunnel testing and the other two blades having a span of (380mm) for wind tunnel testing.The two blades were connected by suitable mechanism in order to be fixed in the wind tunnel protractor and rotated in the required stagger angle. The cascade was tested in an open type low-speed subsonic (Mach number=0.117) wind tunnel, for Reynolds number (Re=239605) based on maximum velocity (35 m/s) and airfoil chord length. The total and static pressures were measured in selected points between the two blades for stagger angles of (4 0 , 0 0 ,- 4 0 ,-8 0 and -120) by using a multi-tube manometer and a pitot static tube. The small blade (90mm span) is tested in the smoke tunnel to visualize the real behavior of flow separation. The theoretical work includes using the software FLUENT (V6.2) to simulate the flow between the two blades. The study shows that the flow separation begins when the cascade are inclined at a stagger angle of (- 4 0 ) on the suction side of the lower blade at a position (96%chord experimentally and 98%chord theoretically). Then, the separation zone increases with increased stagger angle (in clockwise direction) and reach to the position (61%chord experimentally and 63%chord theoretically) at a stagger angle (-12 0 ).These results are validated by a smoke tunnel tests.This separation affects the performance of the compressor, where the static pressure ratio ( Sep /Sip ) decreases as the separation zone gets bigger. The range of working stagger angle is then calculated. It was found in the range (-18 0 to 36 0 ). The flow behavior between the two blades shows that the blade-to-blade configuration works as nozzle-diffuser. The theoretical results were compared with the experimental results and good agreement was obtained.